Analisis respon netizen terhadap program makan bergizi gratis di youtube tempo.co - Laupa, Nurfadila; Iskandar, Iskandar; Sumai, Sumarni; Asmar, Afidatul; Wahyuddin, Wahyuddin (Universitas Garut, 2026)
Abstract This study analyzes the narratives and responses of netizens to the controversial social program